Techno-economic assessment of the horizontal geothermal heat pump systems: A comprehensive review - Cui, Yuanlong; Zhu, Jie; Ssennoga, Twaha; Chu, Junze; Bai, Hongyu; Huang, Kuo; Chen, Xiangjie; Zoras, Stamatis; Soleimani, Zohreh (Energy Conversion and Management, 2019)
Geothermal heat pump has been widely recognized as one of the promising technologies for building applications because of its high energy efficiency and low operating expense, however the high capital investment and installation costs discourage building owners to choose such a system. The horizontal geothermal heat pump system with reduced cost is a viable option that would be utilized widely, the aim of this paper is to catalogue and critique a range of effective approaches for the horizontal geothermal heat pump systems in different regions based on techno-economic assessment data. A ground heat exchanger is a vital component of the horizontal geothermal heat pump. The state-of-the-art analytical and numerical models of the linear-loop, slinky-coil and spiral-coil ground heat exchangers are generalized, in addition to their advantages and disadvantages. A large number of economic evaluation methods for analysing the financial performance of the horizontal geothermal heat pump system are presented. At the end, the standpoints, recommendations and potential future study on the horizontal geothermal heat pump system are deliberated.
Keywords: Horizontal geothermal heat pump; Ground heat exchanger; Analytical models